Positioning lifelong learning in aquaculture: challenges and opportunities - Eleftheriou, Margaret (2015)
Lifelong learning has been one of the building blocks of the Bologna Process since 1999. The Thematic network AQUA-TNET (Aquaculture, Fisheries and Aquatic Resource Management TN—2008–2011—142245-LLP-1-2008-1-BE-ERASMUS-ENW) in its response to each development has made a significant contribution to the network members’ knowledge and understanding of the different aspects concerned in the provision of university lifelong learning. Various definitions and interpretations of the concept led to relatively slow implementation of lifelong learning in many European universities; however, the EUA European Universities Charter of Lifelong Learning Surveys undertaken by AQUA-TNET showed that the AQUA-TNET approach has successfully incentivised its partners, since a higher percentage of AQUA-TNET partners (54 %) have a LLL strategy in place than the HE organisations surveyed by the EUA (average 39 %).